Using a Learning Collaborative Strategy With Office-based Practices to Increase Access and Improve Quality of Care for Patients With Opioid Use Disorders. Issue 2 (March 2016) - Nordstrom, Benjamin R.; Saunders, Elizabeth C.; McLeman, Bethany; Meier, Andrea; Xie, Haiyi; Lambert-Harris, Chantal; Tanzman, Beth; Brooklyn, John; King, Gregory; Kloster, Nels; Lord, Clifton Frederick; Roberts, William; et al.
Abstract : Objectives: Rapidly escalating rates of heroin and prescription opioid use have been widely observed in rural areas across the United States. Although US Food and Drug Administration-approved medications for opioid use disorders exist, they are not routinely accessible to patients. One medication, buprenorphine, can be prescribed by waivered physicians in office-based practice settings, but practice patterns vary widely. This study explored the use of a learning collaborative method to improve the provision of buprenorphine in the state of Vermont. Methods: We initiated a learning collaborative with 4 cohorts of physician practices (28 total practices). The learning collaborative consisted of a series of 4 face-to-face and 5 teleconference sessions over 9 months. Practices collected and reported on 8 quality-improvement data measures, which included the number of patients prescribed buprenorphine, and the percent of unstable patients seen weekly. Changes from baseline to 8 months were examined using a p-chart and logistic regression methodology. Results: Physician engagement in the learning collaborative was favorable across all 4 cohorts (85.7%). On 6 of the 7 quality-improvement measures, there were improvements from baseline to 8 months. On 4 measures, these improvements were statistically significant ( P < 0.001). Importantly, practice variation decreased over time on all measures. The number of patients receiving medication increased only slightly (3.4%). Conclusions: Results support the effectiveness of a learning collaborative approach to engage physicians, modestly improve patient access, and significantly reduce practice variation. The strategy is potentially generalizable to other systems and regions struggling with this important public health problem.